Physiological and hormonal responses to successive taekwondo combats - Bridge, C. A.; McNaughton, L. R.; Close, G. L.; Drust, B. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Recent research into the physiological demands of Taekwondo has resulted in significant advances in our understanding of the energetic requirements of a single Taekwondo combat (Bridge et al. 2009; Chiodo et al. 2011). During a championship event, however, competitors may be required to compete in several combats during a single day. The aim of this study was to examine the physiological and hormonal responses to successive Taekwondo combats using an ecologically valid time structure. Methods: Ten male international Taekwondo competitors (mean ± SD, age 19 ± 3 years, body mass 62.3 ± 2.6 kg, height 1.72 ± 0.04 m, competition experience 6 ± 1 years) took part in a simulated championship event. During the event, the competitors performed four combats that were interspersed with different recovery intervals (63 ± 4, 31 ± 3 and 156 ± 5 minutes respectively). Each combat comprised three two-minute rounds with one-minute rest separating each round. Heart rate (HR) was recorded at 5 s intervals during the combats. Venous blood samples were obtained immediately before and after each combat to determine plasma concentrations of lactate, glucose, glycerol, NEFA, epinephrine and norepinephrine. Results: Significant reductions in plasma lactate (13.9 ± 4.2 vs. 10.5 ± 3.2 mmol/l; P < .05) and a trend for diminished norepinephrine (21.8 ± 12.8 vs. 16.1 ± 7.7 nmol/l; P = .06) were evident between combat 1 and 4. These responses did not appear to be influenced by the different recovery intervals. In contrast, greater (P < .05) plasma glycerol (202 ± 104 vs. 166 ± 92 ìmol/l), NEFA (0.92 ± 0.24 vs. 0.78 ± 0.33 mmol/l) and reduced (P < .05) epinephrine (10.1 ± 5.5 vs. 12.1 ± 6.3 nmol/l) concentrations were identified in combat 3 following 31 minutes of recovery compared to combat 2, which was preceded by 63 minutes of recovery. Higher (P < .05) mean HR was also identified both before and during combat 3. In the final combat, an extended recovery period of 156 minutes was sufficient to restore plasma NEFA, glycerol and epinephrine to similar concentrations as combats 1 and 2, but higher HR was maintained. Discussion: The metabolic adjustments associated with performing repeated Taekwondo combats in this study are suggestive of an increased shift towards aerobic metabolism and diminished anaerobic energy yield. Interestingly, brief recovery intervals appeared to augment the aerobic requirements of the combat activity and accelerate lipolysis. These findings suggest that both the number of combats and different recovery intervals may play an integral role in regulating metabolic function in Taekwondo competition.